Left ventricular function recovery after revascularization: comparative effects of percutaneous coronary intervention and coronary artery bypass grafting. (November 2018) - Ngu, Janet M.C.; Ruel, Marc; Sun, Louise Y.
Abstract : Purpose of review: In 2013, heart failure with recovered ejection fraction (HFrecEF) was introduced as a new heart failure phenotype. This review provides an overview of HFrecEF and the comparative effects of percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) on left ventricular ejection fraction (LVEF) recovery in patients with ischemic cardiomyopathy. Recent findings: There has been emerging data indicating that LV functional recovery is possible and HFrecEF is associated with improved survival and better quality of life. CABG may be associated with larger improvement in LVEF when compared with PCI. However, there is significant paucity of studies, which directly compare the impact of PCI and CABG on LVEF recovery in the setting of ischemic cardiomyopathy. Summary: LVEF recovery is emerging as an important outcome with demonstrated survival and quality-of-life benefits. Future randomized clinical trials comparing the impact of contemporary PCI and CABG on LVEF recovery are needed in patients with ischemic cardiomyopathy.